The Development of Stock Markets: In Search of a Theory - El Wassal, Kamal A. (International Journal of Economics and Financial Issues, 2013)
This paper aims to provide a framework for the main determinants of stock market development. Assessing stock market development requires not only an understanding of its main determinants but also a clear definition of what “stock market development” means and how progress towards it can be measured. This paper reconsiders the concept of stock market development and suggests five dimensions for assessing it. In addition, it proposes four sets of factors that shape or determine stock market development: supply factors, demand factors, institutional factors and economic policies. While both supply factors and demand factors serve as “building blocks” of the stock market, institutional factors and economic policies serve as “supporting blocks. The paper concludes by emphasizing three principles. First, stock market development is a difficult, complex, multi-faceted, and long-term process. Second, stock market development is only part of the overall development of a country’s financial system. Third, stock market development is mainly a private sector activity. Keywords: Stock Markets Development; Measurement of Stock Market Development; Demand for Stocks; Supply of Stocks; Institutional Factors JEL Classifications: G1; G15; G18; G19